A most peculiar book: the inherent strangeness of the Bible - Swenson, Kristin M. (Oxford scholarship online, 2021)
Kristin Swenson addresses the dirty little secret of biblical studies that the Bible is a weird book. It is full of surprises and contradictions, unexplained impossibilities, intriguing supernatural creatures, and heroes doing horrible deeds. It does not provide a simple worldview: what 'the Bible says' on a given topic is multi-faceted, sometimes even contradictory. Yet, Swenson argues, we have a tendency to reduce the complexities of the Bible to aphorisms, bumper stickers, and slogans. Swenson helps readers look at the text with fresh eyes.